1997
DOI: 10.4141/a96-068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary flaxseed on broiler growth, erythrocyte deformability, and fatty acid composition of erythrocyte membranes

Abstract: Bond, J. M., Julian, R. J. and Squires, E. J. 1997. Effect of dietary flaxseed on broiler growth, erythrocyte deformability, and fatty acid composition of erythrocyte membranes. Can. J. Anim. Sci. 77: 279-286. The effectiveness of flaxseed as a source of flax oil in broiler diets was determined in two separate experiments. Broiler growth, fatty acid composition of erythrocyte membranes and hematological variables were measured. We first examined the effect of 10, 20 or 30% flaxseed on growth in broilers and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…The haematological results in our study are in agreement with Al-Daraji et al (2010) who showed that flaxseed (source of omega-3) increased erythrocyte number, PCV, Hb and leukocyte number. Our results are also in agreement with some of the previous reports (Bond et al;Kadhim, 2010;Radwan et al;Jameel, 2013;Al-Zuhairy and Jameel, 2014). The increase of antibody titer against ND virus could be due to omega-3 components are important for the development of the immune cell structure and eicosanoid formation.…”
Section: Discussionsupporting
confidence: 94%
“…The haematological results in our study are in agreement with Al-Daraji et al (2010) who showed that flaxseed (source of omega-3) increased erythrocyte number, PCV, Hb and leukocyte number. Our results are also in agreement with some of the previous reports (Bond et al;Kadhim, 2010;Radwan et al;Jameel, 2013;Al-Zuhairy and Jameel, 2014). The increase of antibody titer against ND virus could be due to omega-3 components are important for the development of the immune cell structure and eicosanoid formation.…”
Section: Discussionsupporting
confidence: 94%
“…The inconsistence might be due to the differences among the trial designs of those researches. The relatively higher breast muscle weight in CO, CL1, and CL2 treatments may be related with that the diets containing corn oil were more beneficial to the breast muscle development of broiler chickens, or that the antinutritional factors in linseed oil had some negative effects on the breast muscle development of broilers (Bond et al 1997). It was reported by Brue and Latshaw (1985) that daily heat production was lesser when corn oil was fed to broiler chickens.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to these supplements, methionine and cystine (M + C) were also added to fulfil the requirements (BIS 1992). or whole form reduced the body weight and FCR. Bond et al (1997) concluded that flaxseed was not a practical oil source, as more than 10% of flaxseed in the diet caused a significant performance reduction. Shen et al (2005) also observed lower weight gain and poor feed conversion efficiency in the birds fed with flaxseed supplemented diet as compared to canola or extruded full-fat soybean-based diets.…”
Section: Growth Performancementioning
confidence: 99%